Comparative Effectiveness of Ampicillin/Sulbactam versus Cefazolin as Targeted Therapy for Bacteremia Caused by Beta-Lactamase-Producing Methicillin-Sensitive Staphylococcus aureus: A Single-Center Retrospective Study - Jun Hirai; Nobuhiro Asai; Mao Hagihara; Takaaki Kishino; Hideo Kato; Daisuke Sakanashi; Wataru Ohashi; Hiroshige Mikamo (MDPI AG, 2022)
Cefazolin (CFZ) is the first-line treatment for beta-lactamase-producing methicillin-sensitive Staphylococcus aureus (BP-MSSA) infection. In 2019, Japan experienced a CFZ shortage because of foreign object inclusion in a batch. Ampicillin/sulbactam (SAM) was preferred in many cases as definitive therapy for the treatment of BP-MSSA bacteremia to preserve broad-spectrum antibiotic stock. However, there are no previous studies reporting the clinical efficacy of SAM for BP-MSSA bacteremia. We aimed to compare the clinical efficacy and adverse effects of SAM versus CFZ in patients with BP-MSSA bacteremia. In total, 41 and 30 patients treated with SAM and CFZ, respectively, were identified. The baseline characteristics were similar in both groups. No significant differences were observed in length of hospital stay and all 30-day mortality between the two groups (p = 0.270 and 0.643, respectively). Moreover, no intergroup difference in 90-day mortality was found (hazard ratio 1.02, 95% confidential interval 0.227-4.53). Adverse effects, such as liver dysfunction, were less in the CFZ group than in the SAM group (p = 0.030). Therefore, in cases of poor CFZ supply or in patients allergic to CFZ and penicillinase-stable penicillins, SAM can be an effective therapeutic option for bacteremia due to BP-MSSA with attention of adverse effects, such as liver dysfunction.